The Gothic Representations of the City through the Fl?neur in Victorian Literature - Chebil, Sana (International Journal of Language and Literary Studies, 2021)
The Victorian Gothic moved away from old and conventional themes and spaces of early Gothic novels such as ruined castles and evil villains into more realistic spaces and characters that went hand in hand with the issues of the era. While the conventional Gothic space centered on the castle or other forms of old buildings, the city was an important component in Victorian Gothic imagery. In an era of growing mediation between the city and the urban dwellers, the gothic representations of the urban space in Victorian literature highly depended on the ’eye’ of the its fl?neurs, or walkers who see, interpret, and produce the city. The fascination with modes of perceiving and seeing the mystery of the puzzling visual experience are evident in a wide variety of the nineteenth and twentieth-century theories and researches on the urban space. The focus of this paper is to graft some insights into debate on urban visuality and other related tropes that provide a range of perspectives on the field of the visual and perception of the city. Then, drawing from Victorian novels, this paper examines Dickens’s portrayals of urban subjects such as Gothic fl?neurs who produce the city as a Gothic place.